Hair steroid before and after COVID-19 in preschoolers : the moderation of family characteristics - Berger, Éloise; Larose, Marie-Pier; Capuano, France; Letarte, Marie-Josée; Geoffroy, Marie-Claude; Lupien, Soni; Brendgen, Mara; Boivin, Michel; Vitaro, Frank; Tremblay, Richard; Masse, Benoît; Côté, Sylvana; et al. (Elsevier, 2025)
Background: Frequent or prolonged exposure to stressors may jeopardize young children’s health. The onset of the COVID-19 pandemic, coupled with disruptions in daily routines and social isolation resulting from public health preventive measures, have raised concerns about its potential impact on children’ experienced stress, particularly for young children and vulnerable families. However, whether the pandemic was accompanied by changes in physiological stress remains unknown as perceived stress is not a good proxy of physiological stress. This study examined if preschoolers showed increasing hair steroid concentrations following the onset of the COVID-19 pandemic and whether family characteristics may have exacerbated or buffered these changes.
Methods: 136 preschoolers (2-4 years) provided hair for steroid measurement (cortisol, dehydroepiandrosterone (DHEA), cortisone, cortisol-to-DHEA ratio, cortisol-to-cortisone ratio) in October-November 2019 (T0) and in July-August 2020 (T1). A 2-centimeter hair segment was analyzed, reflecting steroid production over the two months leading up to collection. Family income, conflict resolution and lack of cohesion, as well as parents’ COVID-19 stress were reported by parents. Linear mixed models for repeated measures and Bayes factors were used.
Results: No significant changes were noted from before to after the onset of the COVID-19 pandemic for most hair steroids. However, a moderating role of family conflict resolution was noted. Children living with parents with a better ability to resolve conflicts had lower levels of DHEA compared to those who had more difficulty managing conflicts. Additionally, lower levels of family cohesion and income were linked to some steroids, especially DHEA, suggesting that these factors may relate to children’s physiological stress. Finally, boys had higher DHEA levels than girls.
Conclusion: Our findings suggest that stress biomarkers were comparable from before to during the COVID-19 pandemic. This observation holds true despite the pandemic being perceived by many as a novel, unpredictable, and potentially threatening event. Findings further suggest that family characteristics are associated with hair steroid, especially DHEA, which deserves further investigation.